EVALUATION OF ROSELLE BASED ON THE INTERNAL TRANSCRIBED SPACER SEQUENCE OF RRNA GENE - Park, Se Hee; Ginibun, Florence C.; Roh, Mark S.; Li, Ming-Xi; Suh, Jeung Keun; Joung, Young Hee (Emirates Journal of Food and Agriculture, 2015)
Genetic differences in 5-lobed leaf Roselle (Hibiscus sabdariffa L.) collected from China, Malaysia, Sudan, and USA were evaluated by the sequence of nuclear internal transcribed spacer 1, 2 regions in rRNA gene (ITS 1, 2 regions). A total of 27 samples were subjected to polymerization chain reaction (PCR) and 729 bp bands were amplified in all samples. Samples were divided into 4 groups based on the single nucleotide polymorphisms at 71, 91, and 249 of the 729 bp band. However, no variations among samples collected from different geographic origins of H. sabdariffa are observed.